1982
DOI: 10.1063/1.443354
|View full text |Cite
|
Sign up to set email alerts
|

Near Hartree–Fock calculation of the H+H2 potential energy surface

Abstract: The SCF potential energy surface for H+H2 is reported for atom–molecule distances R in the range 2.5–6.0a0 and diatomic bond lengths r between 1.2a0 and 1.6a0. The leading harmonic components V0(R, r) and V2(R, r) are obtained. The SCF energies are estimated to be within 2 meV of the Hartree–Fock limit, while the error in V0 is estimated to range from 0 to 7 meV, due mainly to the neglect of higher harmonic components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The other observation refers to the quality of the four Gaussian basis sets, which give very similar results. We conclude that the SiegbahnÈLiu basis set is quite adequate for the purpose of the present work albeit being signiÐcantly smaller than that of Lewchenko et al 21 Thus, it will be employed for the remaining calculations reported in this work.…”
Section: Ab Initio Calculationsmentioning
confidence: 97%
“…The other observation refers to the quality of the four Gaussian basis sets, which give very similar results. We conclude that the SiegbahnÈLiu basis set is quite adequate for the purpose of the present work albeit being signiÐcantly smaller than that of Lewchenko et al 21 Thus, it will be employed for the remaining calculations reported in this work.…”
Section: Ab Initio Calculationsmentioning
confidence: 97%